Early remodeling and loss of light-induced dilation of retinal small arteries in CADASIL - Paques, Michel; Krivosic, Valérie; Castro-Farias, Daniela; Dulière, Cédric; Hervé, Dominique; Chaumette, Céline; Rossant, Florence; Taleb, Abbas; Lebenberg, Jessica; Jouvent, Eric; Tadayoni, Ramin; Chabriat, Hugues (Journal of cerebral blood flow and metabolism, 2024)
A major hurdle to therapeutic development in cerebral small vessel diseases is the lack of in-vivo method that can be used repeatedly for evaluating directly cerebral microvessels. We hypothesised that Adaptive Optics (AO), which allows resolution images up to 1-2 μm/pixel at retinal level, could provide a biomarker for monitoring vascular changes in CADASIL, a genetic form of such condition. In 98 patients and 35 healthy individuals, the wall to lumen ratio (WLR), outer and inner diameter, wall thickness and wall cross-sectional area were measured in a parapapillary and/or paramacular retinal artery. The ratio of vessel diameters before and after light flicker stimulations was also calculated to measure vasoreactivity (VR). Multivariate mixed-model analysis showed that WLR was increased and associated with a larger wall thickness and smaller internal diameter of retinal arteries in patients. The difference was maximal at the youngest age and gradually reduced with aging. Average VR in patients was less than half of that of controls since the youngest age. Any robust association was found with clinical or imaging manifestations of the disease. Thus, AO enables the detection of early functional or structural vascular alterations in CADASIL but with no obvious link to the clinical or imaging severity.